KELVIN PROBE SELF-CALIBRATION MODE FOR SEMICONDUCTOR WAFERS PROPERTIES MONITORING - R. I. Vorobey; O. K. Gusev; A. L. Zharin; A. N. Petlitsky; V. A. Pilipenko; A. S. Turtsevitch; A. K. Tyavlovsky (Приборы и методы измерений, 2015)
Improvement of repeatability and reliability of semiconductor wafers properties monitoring with a probe charge-sensitive methods is achieved by realization of Kelvin probe self-calibration mode using a wafer’s surface itself as a reference sample. Results of wafer surface scanning are visualized in the form of parameter distribution color map. A method of measurements based on Kelvin probe self-calibration mode is realized in a measurement installation for non-destructive non-contact monitoring of semiconductor wafer defects. Method can be used to define defects’ physical properties including minority carrier diffusion length and lifetime, trapped charge density and energy distribution etc.